Experiences of Patient-Centered Care Among Older Community-Dwelling Australians - Hobden, Breanne; Mansfield, Elise; Freund, Megan; Clapham, Matthew; Sanson-Fisher, Rob (Frontiers in Public Health, 2022)
Background Older adults represent the largest consumers of health care. It is, therefore, important that they receive adequate patient-centered care to empower them to be proactive in managing their health. Aims This study examined the proportion of older community-dwelling individuals who report receiving patient-centered care during healthcare consultations. Methods A cross-sectional study was conducted with 117 clients of an Australian aged care provider. Clients completed a survey examining their perceptions of whether they received patient-centered care (11-items) from healthcare professionals. Results The mean number of patient-centered care items reported was 8.7 (±3.1). Speaking to the patient with respect was the item most often reported to be patient-centered (94%). Asking patients about treatment goals or expectations (62%) and how involved they would like to be in treatment (67%) were the items least reported to be patient-centered. Conclusion Older adults perceived some important aspects of care were not provided with a patient-centered approach. There is a need to improve healthcare providers' elicitation of older patients' care preferences, enabling patients to determine their level of involvement in their health management.